A modified Arrhenius model for as-quenched Al-Mg-Si alloy considering the effect of cooling rate. Issue 5 (5th October 2020) - Guo, Ruichao; Wu, Jianjun; Ren, Yinxiang
Abstract : Purpose: Accurate prediction of residual stress requires precise knowledge of the constitutive behavior of as-quenched material. This study aims to model the flow stress behavior for as-quenched Al-Mg-Si alloy. Design Methodology Approach: In the present work, the flow behavior of as-quenched Al-Mg-Si alloy is studied by the hot compression tests at various temperatures (573–723 K), strain rates (0.1–1 s −1 ) and cooling rates (1–10 K/s). Flow stress behavior is then experimentally observed, and an Arrhenius model is used to predict the flow behavior. However, due to the fact that materials parameters and activation energy do not remain constant, the Arrhenius model has an unsatisfied prediction for the flow behavior. Considering the effects of temperatures, strain rates and cooling rates on constitutive behavior, a revised Arrhenius model is developed to describe the flow stress behavior. Findings: The experimental results show that the flow stress increases by the increasing cooling rate, increasing strain state and decreasing temperature. In comparison to the experimental data, the revised Arrhenius model has an excellent prediction for as-quenched Al-Mg-Si alloy. Originality Value: With the revised Arrhenius model, the flow behaviors at different quenching conditions can be obtained, which is an essential step to the residual stress prediction when the model is implemented in a finite element code, e.g. ABAQUS, in the future.